26 marathons : what I learned about faith, identity, running, and life from my marathon career - Keflezighi, Meb; Douglas, Scott, 1964- (Rodale, 2019)
"Four-time Olympic marathoner Meb Keflezighi shares his lessons on life, family, faith, and running through a reflection on each of the 26 marathons he's run in his storied career. When four-time Olympian Meb Keflezighi ran his final marathon in New York City on November 5, 2017, it marked the end of an extraordinary distance-running career. Meb will be remembered as the only person in history to win both the Boston and New York City marathons as well as an Olympic marathon silver medal. Meb's last marathon was also his 26th, and each of those 26 marathons has come with its own unique challenges, rewards, and outcomes for him. Through focused narrative, Meb describes key moments and triumphs that made each marathon a unique learning experience and shows runners--whether recreational or professional--how to apply the lessons he's learned to their own running and lives. Chronologically organized by marathon, 26 Marathons offers wisdom Meb has gleaned about life, family, identity, and faith in addition to tips about running, training, and nutrition. Equal parts inspiration and practical advice, this book will provide readers an inside look at the life and success of one of the greatest runners living today"--